DEVELOPING BUSINESS ENGLISH MODULE BASED ON OUTCOME BASED LEARNING APPROACH - Taufiq Akbar Alfajri; Trisna Andarwulan; Aulia Luqman Aziz (Universitas Brawijaya, 2022)
This research aimed to develop an English module for Business Administration Department students. This research is a research and development or Research and Development. The learning product that will be developed is an English learning module to improve student competence with an outcome-based education approach. The trial product was then evaluated by several parties, including expert and lecturers. Based on the results of the group test, there is an effect of developing students' English skills using the English for Business Administration module with those who do not use the module. And after a comparison test was carried out between class A and class B (experimental class) it was found that the English language skills of business administration students were better, both in terms of reading and vocabulary, listening comprehension, writing skills and speaking fluency. Thus, the English for Business Administration module is able to overcome the problems that have been faced by business administration students in terms of mastering business administration English.